Roads and Rivals : The Political Uses of Access in the Borderlands of Asia - Ispahani, Mahnaz Z. (London I.B Tauris & Co. Ltd. Publishers, 1989)
Routes and states; Baluchistan and its environs - the motives for access; Afghanistan, Pakistan and the Soviet Union - the price of access; the Karakoram and Himalayan borderlands - the consequences of access; the politics of routes.
Include Index and Bibliography
Keywords: Politics and government -- Roads -- Asia